Perlindungan Konsumen Dalam Hukum Bisnis - Fiorenza Adelia Dome; Khairunnisa; Miranda; Muhammad Aditya Osyra; Muhammad Ainur Ridho; Helfira citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study discusses consumer protection within the framework of business law in Indonesia, focusing on the imbalance of legal positions between consumers and business actors in modern economic activities. Rapid business development, including conventional and digital transactions, often places consumers in a vulnerable position due to limited information, unequal bargaining power, and the use of standard contracts imposed unilaterally by business actors. The purpose of this research is to analyze the concept and regulation of consumer protection, identify forms of legal protection provided to consumers, and examine the role of consumer protection law in creating a balance of interests between consumers and business actors. This research employs a normative juridical method with a descriptive-analytical approach, using statutory regulations, legal literature, and previous studies as sources of data. The results show that consumer protection in Indonesia is comprehensively regulated under Law Number 8 of 1999 concerning Consumer Protection, which guarantees consumer rights, regulates business actors’ obligations, and provides dispute resolution mechanisms. Effective implementation of consumer protection law is essential to ensure legal certainty, enhance consumer trust, and promote fair and sustainable business practices.